Rabies-preventive health program for mothers in maternal and child health centers: quasi experimental study - Samia Ibrahim Mabrouk Baraka; Rania Abd Elmohsen Abo El Nour; M. A. Abdelzaher; Eman Mahmoud Seif El–Nasr (Journal of Health, Population and Nutrition)
Abstract Background Rabies spreads to people and animals via saliva, usually through bites, scratches, or direct contact with mucosa (e.g. eyes, mouth, or open wounds). Rabies remains a major public health problem in Egypt, with an estimated 60 people dying annually from the disease. Aim The aim of this study was to assess the effect of preventive program on mothers' awareness for prevention of rabies. Study design Quasi-experimental research design was utilized in this study. Setting This study was conducted at three major Maternal and child centers (Botors, Embaby and Segar) in Tanta City. Sample A total sample of 150 mothers who attended the child clinic with children aged 6–12 years. Tools Researchers developed three tools for data collection. The tools underwent content validity assessment, and their internal consistency was evaluated using Cronbach's alpha coefficient. Structured interviewing questionnaire for assessment of mothers’ knowledge, attitudes and practices regarding rabies Tool I, Mothers' knowledge regarding rabies questionnaire. This tool consisted of two parts: demographic characteristics of the studied mothers and mothers’ knowledge about rabies. Tool II, Rabies attitudinal Likert scale. Tool III, Mothers reported practice Questionnaire. Results From the obtained results, it was found that, a statistically significant correlation was found between mothers' total knowledge scores, attitude and total practice scores, both before and after the implementation of the rabies prevention program. Conclusion It was concluded that the rabies- preventive health program had a positive impact on mother’s knowledge, attitude and practices regarding rabies. The mean knowledge score improved from 14.08 before preventive program to 20.90 one month posttest. Negative attitude of the studied mothers was 48% before program but it reduced to 1.3% one month after preventive program. Only 13.35% of the participants had satisfactory level of practice before program and increased to 83.30% one month posttest. Recommendations Dissemination of the program through mass media campaigns and community outreach activities to enhance public knowledge, improve attitudes, and promote better practices regarding rabies prevention and control measures.